Precise Detections of Solar Particle Events and a New View of the Moon. Issue 1 (6th January 2020) - Wilson, Jody K.; Spence, Harlan E.; Schwadron, Nathan A.; Case, Anthony W.; Looper, Mark D.; Jordan, Andrew P.; de Wet, Wouter; Kasper, Justin
Abstract: We have invented a new method for detecting solar particle events using data from the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) on the Lunar Reconnaissance Orbiter (LRO). Using a simple function of the total particle detection rates from four of CRaTER's six detectors, we can precisely identify solar energetic particle event periods in the CRaTER data archive. During solar quiet periods we map the distribution of a mare‐associated mixture of elements in the lunar regolith using this new method. The new map of the moon probably reflects an as‐yet unknown combination of lunar albedo protons, neutrons, and gamma rays, and most closely resembles Lunar Prospector maps of gamma rays characteristic of thorium and iron. This result will lead to multiple follow‐up studies of lunar albedo particles and may also contribute to the study of diurnally varying hydrogenation of the lunar regolith. Key Points: The CRaTER instrument on LRO can detect and quantify small solar particle events with a simple new analysis technique Our new lunar map of albedo radiation resembles gamma ray maps from Lunar Prospector Follow‐up studies will investigate contributions from neutrons, protons, and gamma rays, and signatures of hydrogen in lunar regolith